2004
DOI: 10.2139/ssrn.567241
|View full text |Cite
|
Sign up to set email alerts
|

Counting Chickens when they Hatch: The Short-Term Effect of Aid on Growth

Abstract: Recent research yields widely divergent estimates of the cross-country relationship between foreign aid receipts and economic growth. We propose and test two reasons for this divergence, both of which relate to the timing of effects between aid and growth. First, these studies have insufficiently considered the lag with which aid might affect growth, particularly certain kinds of aid. Second, they have sought to reduce the bias from contemporaneous reverse causation with the use of instrumental variables that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
266
2
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(294 citation statements)
references
References 23 publications
(28 reference statements)
15
266
2
11
Order By: Relevance
“…nomic growth. Recent research studies Clemens et al 2004;Rajan and Subramanian 2005) have attempted to capture this phenomenon by incorporating aid into a well-established aid-growth regression using the per capita real GDP (PCGDP) as the dependent variable. We used data covering a 33-year period , which are available on a consistent basis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…nomic growth. Recent research studies Clemens et al 2004;Rajan and Subramanian 2005) have attempted to capture this phenomenon by incorporating aid into a well-established aid-growth regression using the per capita real GDP (PCGDP) as the dependent variable. We used data covering a 33-year period , which are available on a consistent basis.…”
Section: Methodsmentioning
confidence: 99%
“…Under certain circumstances with the rise in the volume of aid there were diminishing returns along with the presence of a conditional, positive relationship. While Clemens, Radelet, and Bhavnani (2004) indicated the existence of a positive relationship between aid and growth, a study by Rajan and Subramanian of IMF (2005) found no evidence of aid having either a positive or a negative effect on growth. This study, along with another study by Raghuram and Subramanian (2005), indicated that aid-receiving countries would have been under the influence of the well-known "Dutch disease effect," which is reflected in the appreciation of real exchange rate, adversely affecting the competitiveness of exports, thereby weakening their economic growth.…”
Section: Introductionmentioning
confidence: 98%
“…As a caveat, Banerjee et al also caution that the time-frame was only 15-18 months. This is likely to be insufficient for health, education, and gender empowerment effects to show up (Clemens et al 2004). So the evidence itself is probably inconclusive.…”
Section: Self-help Organizationsmentioning
confidence: 99%
“…So too is economic growth. In a noted review of aid's effectiveness, Clemens et al (2004) divided it into: longer term (like aid to support democracy) versus shorter term (like building and other infrastructure projects). The review focused on shorter term aid.…”
Section: Much Of the Seemingly Incomprehensible Behavior Of Subsistenmentioning
confidence: 99%
“…Good policies in this context refer to low infl ation, increased trade openness and small budget defi cits or surpluses. Indeed, the BD study has stimulated further researches such as Clemens, Radelet and Bhavnani (2004), Collier and Dehn (2001), Dalgaard and Hansen (2001), Guillaumont and Chauvet (2004). Another recent study by Mwanza and Selin (2004) have also introduced the idea that deeper fi nancial markets or in other words, fi nancial development in aid-recipient countries facilitate the management of aid fl ows, 4 thereby enhancing absorption capacity and hence better aid effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%